Intergovernmental Relations in Handling People with Social Welfare Problems in the City of Pekanbaru - Khotami; Monalisa; Rizky Setiawan; Budi Mulianto; Chandra Tegas Widjiantoro (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
This research examines the relationship between governments in dealing with people with social welfare problems in Pekanbaru City, where researchers found symptoms of an increasing number of street children and also children in conflict with the law as part of people with social welfare problems. This research aims to determine the extent of the role of regional apparatus organizations and organizational units in the Pekanbaru city regional government in dealing with people with social welfare problem status. This research was conducted using a qualitative approach by presenting data related to intergovernmental relations which includes leading aktors, central features, authority patterns and conflict resolution methods in handling people with social welfare problems. The results of the research show that the lack of regularity and interaction between related agencies/departments in dealing with children who are in conflict with the law, the lack of attention and handling of people with social welfare problems, especially children who are in conflict with the law, has caused an increasingly massive growth in the number of children involved in legal cases in Pekanbaru City. The synergy and commitment of each relevant party in the Pekanbaru City Government is an alternative solution to problems for people with social welfare problems in the City of Pekanbaru by strengthening interactions between interested actors in the Social Service, Regional Indonesian Child Protection Commission and other related parties.